Research on PaaS Platform Opening Capability of Smart Pipe - 赵学军; 陆钢; 何震苇 (Dianxin kexue)
In the time of mobile internet, the platform has become the focus of competition in the field of operators and internet companies, the open core capabilities has become the key to success of the platform. Smart pipe is a natural advantage capability of operators, and need to access to the PaaS platform to make more value. The present situation of PaaS platform and smart pipe capability were briefly introduced, the possible business models of combination with smart pipe and PaaS platform were analyzed, technical proposal the solution on operator PaaS platform opening smart pipe capability was put forward, and finally the prospect of development of the platform was given.